Sowa-Rigpa (Amchi/Buddhist Medicine): A Review (International Journal of Ayurveda and Pharma Research, 2022)
Sowa-rigpa is known as Amchi or Buddhist medicine or Tibetan system of medicine which is primarily based on Buddhist philosophy. It is the fact that basic concepts of Sowa-Rigpa and Ayurveda are almost same and it seems that there is inter-relation among these two traditional systems of Indian Medicine. The description of Tridosha, Panchamahabhuta, seven Dhatus, three Malas, week wise embryological development are same. In Sowa-Rigpa, it has been mentioned that we all are sick due to ignorance as according to Buddhist philosophy, Ignorance is the cause of sufferings. The relation between ignorance and suffering as per the Sowa-Rigpa may be the unique concept which may show the path for human-beings to eradicate all human sufferings i.e., ultimately to walk on the path of Nirvana which is the goal of Buddhist philosophy and Moksha according to Ayurveda.